1947
DOI: 10.1084/jem.86.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Bacterial Pyrogens

Abstract: In a study of the febrile responses of rabbits to repeated intravenous injections of pyrogenic substances from Eberthella typhosa, Serratia marcescens, and Pseudomonas aeruginosa, the following observations were made: 1. A characteristic pattern of response to daily injections of the same dose of pyrogenic material was noted. This consisted of a progressive diminution in febrile response during the 1st week or 10 days, after which an animal responded to each injection with approximately the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
125
0
1

Year Published

1949
1949
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(129 citation statements)
references
References 3 publications
3
125
0
1
Order By: Relevance
“…Recently, Wolff and his associates observed that rabbits pretreated with 6-mercaptopurine readily acquired pyrogenic 5 The complementary observation, i.e. that pyrogenic tolerance wanes despite elevated circulating antibody titers to endotoxin (24), is not as crucial an argument against the importance of circulating antibody since a decrease in those antibodies with protective activity might be masked by a high titer of non-protective antibody (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wolff and his associates observed that rabbits pretreated with 6-mercaptopurine readily acquired pyrogenic 5 The complementary observation, i.e. that pyrogenic tolerance wanes despite elevated circulating antibody titers to endotoxin (24), is not as crucial an argument against the importance of circulating antibody since a decrease in those antibodies with protective activity might be masked by a high titer of non-protective antibody (20).…”
Section: Discussionmentioning
confidence: 99%
“…The reappearance of pyrogenic responsiveness upon resuming the intravenous infusion of endotoxin on day 2 in man, the rapid waning of pyrogenic unresponsiveness after an initial single intravenous bolus of a small quantity (1.0/~g) of endotoxin in rabbits (35), and the need for daily injections of endotoxin to maintain maximum pyrogenic tolerance (24) all suggest that desensitization to endotoxin at the cellular level is transient. Stetson has previously emphasized the parallelism to maintainence of the desensitized state to tuberculin (18).…”
Section: Discussionmentioning
confidence: 99%
“…The failure of tolerant rabbit serum to transfer high levels of pyrogenic tolerance to normal recipients (8,11,29) does not exclude the importance of specific humoral endotoxin inhibitors; such factors, behaving as opsonins, may induce more intense inhibition in conjunction with the generalized RES stimulation that accompanies pyrogenic tolerance in this species. Moreover, quantitative data are not yet available to evaluate the effects of dilution following passive transfer to normal recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of tolerance to LPS was noted early on with respect to the febrile response of the rabbit (Beeson, 1947). It was suggested to be controlled at the cellular level (Greisman et al, 1966) (Freudenberg and Galanos, 1988).…”
Section: Discussionmentioning
confidence: 99%